(untitled) (Journal of Innovation in Academia, 2025)
T.S. Eliot’s seminal modernist poem "The Waste Land" has long been recognized for its intricate web of literary and philosophical allusions, including references to Mahayana Buddhism. This paper aims to examine the presence and significance of the Bodhisattva, a central figure in this tradition, within the poem. Through the lens of Buddha Nature, the fragmented characters and desolate landscapes depicted in "The Waste Land" are re-examined, revealing hidden layers that resonate with the notion of inherent enlightenment in apparent spiritual crisis. The paper explores how Eliot’s engagement with Buddhist philosophy, as reflected through the concept of Buddha Nature, bridges eastern and western worldviews, offering a platform for cross-cultural dialogue and interpretation. It seeks to unravel Eliot’s nuanced exploration of human suffering, the quest for enlightenment, and the interplay between spiritual emptiness and the inherent Buddha Nature. The Bodhisattva’s commitment to guiding others toward enlightenment echoes the potential for transformation.